Correlation between the socio-demographic characteristics and clinical profile with oral manifestations of HIV/AIDS patients - Apriasari, Maharani Laillyza; Aprilyani, Nur; Carabelly, Amy Nindia; Utami, Juliyatin Putri (Universitas Padjadjaran, 2021)
Introduction: Human Immunodeficiency Virus (HIV) exhibits the capability to weaken human immune system. The infected subject will later be more susceptible to suffer from opportunistic diseases when the CD4 cell count is lesser than 200 cell/µL. Oral thrush, periodontal disease and xerostomia are common oral manifestations in AIDS patient which initially indicate the presence of HIV infection. This study was aimed to analyse the correlation between the socio-demographic characteristics and clinical profile with oral manifestations of HIV/AIDS patients. Methods: An analytic study with cross-sectional approach was conducted towards the clinical profile and oral manifestation data of HIV/AIDS patients, which obtained from secondary data in the form of medical record. The 55 samples were taken with total sampling technique. Results: The chi-square test found no significant correlation between HIV/AIDS patients socio-demographic and oral manifestations and several significant correlation of the HIV/AIDS patients' clinical profile with the oral manifestation as follows: the total number of CD4 and ARV therapy duration was significantly correlated with the HIV/AIDS patients with candidiasis and oral thrush (p=0.01); while in patients with periodontal disease was only significantly correlated with the total number of CD4 (p=0.02); and no significant correlation found in HIV/AIDS patients with xerostomia. Conclusion: There is no correlation between HIV/AIDS patients socio-demographic and oral manifestations. There is a correlation between several HIV/AIDS patients clinical profile with the oral manifestation. The number of CD4 cells and the ARV therapy duration was correlated with patients with candidiasis and oral thrush, while in patients with periodontal disease on correlated with the number and CD4 cells. HIV/AIDS patients with xerostomia have no correlation with any of their clinical profile.